2020
DOI: 10.1556/2006.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Should compulsive sexual behavior (CSB) be considered as a behavioral addiction? A debate paper presenting the opposing view

Abstract: Background and aimsCompulsive sexual behavior disorder (CSBD) has been a long debated issue. While formerly the discussion was about whether to regard CSBD as a distinctive disorder, the current debate is dealing with the classification of this phenomenon. One of the prominent voices in this field considers CSBD as a behavioral addiction and proposes CSBD to be called and diagnosed as sexual addiction (SA). This present debate paper will review the existing evidence supporting this view and it will argue again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 81 publications
6
68
0
Order By: Relevance
“…Despite the inclusion of Compulsive Sexual Behavior Disorder (CSBD) in the 11th edition of the International Statistical Classification of Diseases and Related Health Problems (ICD-11; World Health Organization, 2019), it cannot be conclusively determined whether CSBD should be considered as an impulse control, compulsivity-related, or addictive disorder (Kor et al, 2013; Kraus et al, 2016; Potenza et al, 2017; Prause et al, 2017; Sassover & Weinstein, 2020). Similarly, there is no consensus in the literature about the conceptualization of PPU (Bőthe, Tóth-Király, et al, 2019; Ley et al, 2014).…”
Section: Adolescents’ Pornography Usementioning
confidence: 99%
“…Despite the inclusion of Compulsive Sexual Behavior Disorder (CSBD) in the 11th edition of the International Statistical Classification of Diseases and Related Health Problems (ICD-11; World Health Organization, 2019), it cannot be conclusively determined whether CSBD should be considered as an impulse control, compulsivity-related, or addictive disorder (Kor et al, 2013; Kraus et al, 2016; Potenza et al, 2017; Prause et al, 2017; Sassover & Weinstein, 2020). Similarly, there is no consensus in the literature about the conceptualization of PPU (Bőthe, Tóth-Király, et al, 2019; Ley et al, 2014).…”
Section: Adolescents’ Pornography Usementioning
confidence: 99%
“…Although it is hard to compare the two studies, based on the data it is quite convincing that while CSB and pornography watching both entail self-criticism and shame, pornographywatching involves also a sense of guilt that alongside with shame takes dominance over self-criticism. Despite the longdebated issue whether CSB should be labelled as a behavioural addiction (Sassover & Weinstein, 2020), it is quite agreeable that CSB shares major elements with addiction such as the uncontrollable action and the adverse result. Addictive behaviours, in general, involve shame but not guilt.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, with respect to altered brain networks and processes neuroimaging research to date seem to support the classification of CSBD as an addictive disorder. However, from the perspective of the six components model of behavioral addictions (salience, mood modification, tolerance, withdrawal, conflict) proposed by Griffits (58), there is still lack of methodological evidence for the existence of such elements as tolerance or withdrawal (59). More studies are indicated to examine this possibility further.…”
Section: Possible Mechanisms Underlying Csbdmentioning
confidence: 99%